Developing a safer- walking android mobile application to support people with dementia - Momeni, Asma (2015)
Nowadays, recent advances in technologies improved our quality of life which can extend average life expectancy. As the number of elderly people increases significantly, their relevant disease grows too. Dementia is one of the most common diseases that mainly elder people are suffering from globally. People with dementia usually wander and put themselves under risks such as becoming lost, damaged, abused or even involved in accidents. In order to minimise these risks, they are required to be controlled by professional caregivers or family members, which cost approximately US$818 billion worldwide. In order to protect patients’ safety, they have been usually locked at home, which may bring negative impacts on their indecency, well-being and autonomy. Various studies have been conducted to address these issues by implementing recent technologies such as GPS, and smartphones. Most of these approaches used GPS to locate the person with dementia, which involve benefits and drawbacks. However, this research was developed to address some of former research’s weakness and offer additional benefits for both patients and caregivers. Within this proposed system, smartphones integrated with GPS, Wi-Fi, mobile data, and Bluetooth enabling caregivers to control the patients remotely. Caregivers would be able to specify a daily time-plan by determining places whether patients are commuting into regularly and allocate these spaces into specific of times. Based on the defined time-plan, patients could visit their destinations independently while being tracked by their phone’s locators indulging available GPS, Wi-Fi or mobile data. If they become out of the defined areas with specific of time, their locations would be share with related caregivers via SMS notifications. This means the patient location only is available for the caregivers in extreme cases not 24 hours a day. This was one of the similar approaches’ limitations that the patients were not satisfied about being located all the day. Besides, the time table provided with the system can support both caregivers and patient to follow their routines. Another issue of recent similar studies was the possibility to leave the phones. In order to address this weakness, iBeacon used in the proposed system. Within evaluation process, various feedbacks were gathered from two different groups. Four professionals in dementia filed assessed the system in terms of its importance in practical terms, and four member of public examined the system usability. It was concluded that the proposed system overcomes some of former studies weaknesses. In addition, it offers various advantages for caregivers, patients and society by reducing the attributed cost, enhancing the feel of independency, and protecting the privacy.